Laser control of electronic exchange interaction within a molecule - Rupprecht, Patrick; Aufleger, Lennart; Heinze, Simon; Magunia, Alexander; Ding, Thomas; Rebholz, Marc; Amberg, Stefano; Mollov, Nikola; Henrich, Felix; Haverkort, Maurits W.; Ott, Christian; Pfeifer, Thomas (Physical review letters, 2022)
Electronic interactions play a fundamental role in atoms, molecular structure and reactivity. We introduce a general concept to control the effective electronic exchange interaction with intense laser fields via coupling to excited states. As an experimental proof of principle, we study the SF6 molecule using a combination of soft x-ray and infrared (IR) laser pulses. Increasing the IR intensity increases the effective exchange energy of the core hole with the excited electron by 50%, as observed by a characteristic spin-orbit branching ratio change. This work demonstrates altering electronic interactions by targeting many-particle quantum properties.